Explicit Solutions of the Whittaker Equation via Discrete Fractional Calculus Operator - Yilmazer, Resat; Ozturk, Okkes (Centre Environment Social & Economic Research Publ-Ceser, 2019)
In our present paper, we attain new solutions in the discrete fractional types of the Whittaker differential equation (homogeneous and non-homogeneous) by applying nabla discrete fractional calculus (DFC) operator. Thus. we have developed a new and different solution method for this equation. Moreover, this method is also a very useful technique to be applied to similar equations.
Keywords: discrete fractional calculus; Whittaker equation; nabla operator